2002
DOI: 10.1007/s00134-002-1507-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury and acute respiratory distress syndrome at the intensive care unit of a general university hospital in Brazil

Abstract: (1) The frequency of ALI was 3.8%, of which the frequency of ARDS was 2.3% and of ALI/non-ARDS 1.5%; (2) The ICU and hospital mortality of ALI patients was 44.0% and 48.0%, respectively; mortality rates of ARDS and ALI/non-ARDS did not differ significantly; (3) Renal and hematological dysfunction were associated with mortality in ALI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
0
8
0
8
Order By: Relevance
“…Additional studies have confirmed that RBC transfusion is an independent risk factor for ALI and ARDS (161)(162)(163)(164).…”
Section: All Efforts Should Be Initiated To Avoid Rbc Transfusion In mentioning
confidence: 88%
“…Additional studies have confirmed that RBC transfusion is an independent risk factor for ALI and ARDS (161)(162)(163)(164).…”
Section: All Efforts Should Be Initiated To Avoid Rbc Transfusion In mentioning
confidence: 88%
“…These results were compared with a previous cohort of 1,301 patients admitted to the same ICU between April 1999 and April 2000 [1]. In both studies all patients were evaluated regarding the presence/development of ALI/ARDS according to the 1994 American–European Consensus Conference.…”
Section: Methodsmentioning
confidence: 99%
“…Our objectives were to compare the ALI/ARDS mortality rates and the ALI mortality risk factors between two cohort studies of the same ICU in different periods of time: 1999/2000 (2000 cohort [1]) and 2004/2007 (2007 cohort).…”
Section: Introductionmentioning
confidence: 99%
“…Como existem poucos estudos epidemiológicos publicados a respeito da LPA e SDRA no Brasil (60) , realizamos este estudo de coorte prospectivo para determinar a incidência acumulada anual, descrever os fatores de risco, variáveis clínicas e fisiológicas e analisar a sobrevida dentro da nossa realidade, nos pacientes admitidos nas UTIs da região da Grande Vitória, no Espírito Santo (ES).…”
Section: Mortalidade Da Lpa E Da Sdraunclassified